Current and novel approaches to vaccine development against tuberculosis - Cayabyab, Mark; Macovei, Lilia; Campos-Neto, Antonio (Frontiers in Cellular and Infection Microbiology, 2012)
Antibiotics and vaccines are the two most successful medical countermeasures that humans have created against a number of pathogens. However a select few e.g., Mycobacterium tuberculosis, the causative agent of tuberculosis (TB) have evaded eradication by vaccines and therapeutic approaches. TB is a global public health problem that kills 1.4 million people per year. The past decade has seen significant progress in developing new vaccine candidates, but the most fundamental questions in understanding disease progression and protective host responses that are responsible for controlling Mtb infection still remain poorly resolved. Current tuberculosis treatment requires intense chemotherapy with several antimicrobials, while the only approved vaccine is the classical viable whole-cell based Bacille-Calmette-Guerin (BCG) that protects children from severe forms of TB, but fails to protect adults. Taken together, there is a growing need to conduct basic and applied research to develop novel vaccine strategies against TB. This review is focused on the discussion surrounding current strategies and innovations being explored to discover new protective antigens, adjuvants and delivery systems in the hopes of creating an efficacious tuberculosis vaccine.